Model-based sonification based on the impulse pattern formulation - Simon Linke and Rolf Bader and Robert Mores (Journal on multimodal user interfaces, 2023)
The most common strategy for interactive sonification is parameter mapping sonification, where sensed or defined data is pre-processed and then used to control one or more variables in a signal processing chain. A well-known but rarely used alternative is model-based sonification, where data is fed into a physical or conceptual model that generates or modifies sound. In this paper, we suggest the Impulse Pattern Formulation (IPF) as a model-based sonification strategy. The IPF can model natural systems and interactions, like the sound production of musical instruments, the reverberation in rooms, and human synchronization to a rhythm. Hence, the IPF has the potential to be easy to interpret and intuitive to interact with. Experiment results show that the IPF is able to produce an intuitively interpretable, natural zero, i.e., a coordinate origin. Coordinate origins are necessary to sonify both polarities of a dimension as well as absolute magnitudes.
Keywords: Interactive sonification; Impulse pattern formulation; Model-based sonification